Factors Affecting Earnings Management of Islamic Banking Companies at the Indonesia Stock Exchange on Publication Year of 2013-2019 - Syarif, Firman; Qorib, Ahmad; Siregar, Saparuddin; Muda, Iskandar (Universitas Pendidikan Ganesha, 2021)
This research was conducted on Islamic banking listed on the Indonesia Stock Exchange from 2013-2019 using secondary data. A saturated data analysis is used in this research. The sample is all Sharia banking companies as many as 12 companies. The results show that Institutional Ownership, Managerial Ownership, Individual Ownership, Foreign Ownership, and the Board of Commissioners have an effect on Earnings Management. Meanwhile, State Ownership, Family Ownership, Public Ownership, Public Accountants, Audit Committee, and Board of Directors have no effect on Earnings Management. Simultaneously all independent variables have an effect on Earnings Management. Given their findings, the authors propose that the practical implication of this research is that earnings management does not occur much in Islamic banks listed on the Indonesian Stock Exchange Earnings Management in the study of Islamic Business Ethics is in the form of deliberate fraud or fraud to achieve certain interests and its nature is not for the benefit of the people or society so it is not allowed because it will have an impact on the survival of the company. But interests that are in a precarious condition that endanger the interests of the public or the state, such as a pandemic outbreak, are allowed because the country is experiencing an economic downturn.